Dural arteriovenous fistulas presenting with reversible dementia are associated with a specific venous drainage. (7th November 2013) - Labeyrie, M. A.; Lenck, S.; Saint‐Maurice, J. P.; Bresson, D.; Houdart, E.
<x xml:space="preserve">Abstract</x> Background and purpose Venous drainage of dural arteriovenous fistula (DAVF) with dementia has never been reported. The aim of this study was to discover if specific vascular conditions exist to develop dementia in patients with DAVF. Methods Venous drainage in patients embolized in our centre between 1996 and 2012 for a DAVF with dementia were qualitatively analyzed and compared with a control group without dementia. Results Eight patients with dementia and 45 control patients were included. The prevalence of dementia was 4%. Diffuse hemispheric white matter lesions on magnetic resonance imaging (MRI) were consistently associated with dementia. Cognitive symptoms dramatically improved after embolization. The consistent angiographic feature in patients with dementia was drainage of the DAVF into both the straight sinus and the superior sagittal sinuses. Only two patients in the control group had similar abnormalities. Conclusions The association of a reflux from the fistula into the straight sinus and the superior sagittal sinuses is a necessary condition to develop such a reversible dementia in DAVF. Venous hypertension in the territory of transparenchymal veins may explain this reversal phenomenon. A rapidly progressive dementia with diffuse white matter lesions on MRI should evoke this diagnosis to the physician.